Physical activity for children with autism in a school setting - Golikova E.M.; Botagariev T.A.; Kubieva S.S.; Оtegenov N.О. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to pinpoint the unique aspects of implementing physical education and sports programs for children with autism spectrum disorder within an educational institution. Methods and structure of the study. The process of examining and summarizing the implementation of physical education and sports programs for children with autism spectrum disorder is underway. The research focuses on children aged 9-10 who attend both special (correctional) schools and mainstream schools. Results and conclusions. The data collected during the testing demonstrate the physical fitness of children with autism spectrum disorder. There is a notable disparity between the examined parameters of children who participate in after-school activities and those who only attend regular classes. The outcomes of the experimental group, in contrast to the control group, improved for girls from 7% to 30% and for boys from 9% to 28%. This underscores the necessity of integrating extracurricular physical education and sports into the subject "Physical Culture" to specifically target the enhancement of motor skills, coordination, self-control of movements, and the ability to maintain a stable posture.